2023
DOI: 10.1177/10998004221151157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Surgical Smoke on the Air Quality and on the Physical Symptoms of Operating Room Staff

Abstract: Background Surgical smoke can be a hazard because e it contains toxic gases with carcinogenic effects that may threaten health. This study aims to determine the effect of surgical smoke containing toxic chemicals on indoor air quality and examine employees’ physical symptoms in the operating room. Method The study was conducted in the operating room between June 2020 and July 2020. In the study, 45 air samples were taken before, during, and after surgery using the active sampling method. Nineteen employees wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…We did not nd an association between total PPM and the detection of pathogens; however, the exposition to certain VOCs can cause serious health effects 31,32 , as many of these compounds are carcinogenic 33 . A previous simulation showed that CO 2 concentration can increase up to ~ 300 PPM when 4 people remain inside the OR for 20 minutes 34 .…”
Section: Discussioncontrasting
confidence: 58%
“…We did not nd an association between total PPM and the detection of pathogens; however, the exposition to certain VOCs can cause serious health effects 31,32 , as many of these compounds are carcinogenic 33 . A previous simulation showed that CO 2 concentration can increase up to ~ 300 PPM when 4 people remain inside the OR for 20 minutes 34 .…”
Section: Discussioncontrasting
confidence: 58%
“…In surgery, the carcinogenicity of surgical smoke has long been considered a serious problem, 12 , 14 , 27 and various smoke evacuators are commercially available. 12 , 24 , 28 , 29 In contrast, in the field of endoscopy, there is less awareness of the dangers of surgical smoke.…”
Section: Discussionmentioning
confidence: 99%